Callous-unemotional behaviors and conduct problems in Chinese preschoolers: the moderating roles of surgency and gender - Zhu, Jingjing; Shu, Xin; Li, Zhuyi; Li, Yan (Frontiers in Psychology, 2024)
Introduction Conduct problems in children are related to callous-unemotional (CU) behaviors. However, results of the relationships between CU behaviors and conduct problems among preschoolers mainly focused on Western countries, no studies have examined whether CU behaviors predict conduct problem in Chinese preschoolers. The primary objective of the current study therefore was to examine the associations between CU behaviors and conduct problems as well as the moderating effects of surgency and child gender in Chinese preschool children. Methods The present study randomly selected 2,154 children (1,043 boys, Mage = 56 months, SD = 10.47) from six kindergartens in Shanghai, People’s Republic of China. Mothers rated children’s surgency and teachers reported children’s CU behaviors and conduct problems. Results Results demonstrated that CU behaviors were positively associated with conduct problems. Surgency and child gender significantly moderated these associations. Specifically, CU behaviors were positively associated with conduct problems, with a stronger effect found for high levels of surgency. CU behaviors had a positive association with conduct problems, with a stronger effect found for boys. Discussion This study indicate that temperament and gender characteristics influence conduct problems in preschoolers who exhibit high levels of CU behaviors. As well, the findings emphasize the significance of considering the meaning and implication of CU behaviors in Chinese culture.